The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.chemrev.9b00839
|View full text |Cite
|
Sign up to set email alerts
|

Functional Supramolecular Polymeric Networks: The Marriage of Covalent Polymers and Macrocycle-Based Host–Guest Interactions

Abstract: Covalent polymers connected by non-covalent interactions constitute a fascinating set of materials known as supramolecular polymer networks (SPNs). A key feature of SPNs is that the underlying covalent polymers endow the resulting self-assembled materials with features, such as structural and mechanical integrity, good processability, recyclability, stimuli-responsiveness, self-healing, and shape memory, that are not recapitulated in the case of classic covalent polymer systems. The unique nature of SPNs deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
354
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 527 publications
(384 citation statements)
references
References 549 publications
2
354
0
1
Order By: Relevance
“…Moreover, supramolecular polymer materials can be combined with covalent polymer materials to achieve functions and uses that are difficult to have for covalent polymer materials. [ 55‐58 ] With these further investigations, both the scientific and social values of supramolecular polymer studies can be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, supramolecular polymer materials can be combined with covalent polymer materials to achieve functions and uses that are difficult to have for covalent polymer materials. [ 55‐58 ] With these further investigations, both the scientific and social values of supramolecular polymer studies can be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the prepared CEs functionalized polymeric gels were investigated for their self-healing properties and stimuli-responsiveness under different stimuli such as cation, anion, and pH-changes. 16 Han et al 51 constructed thermo-and ion-responsive supramolecular hydrogels by incorporating CEs into the poly(N-isopropylacrylamide) (PNIPAM) polymer. The swelling ratio (SR) of the copolymeric hydrogel was decreased in comparison to the pristine PNIPAM.…”
Section: Materials Advances Reviewmentioning
confidence: 99%
“…15 These stimuli-responsive MPs have been utilized for the development of functional materials, which show great potential in sensing, catalysis, hydrogels, and drug (gene) delivery applications. [16][17][18] The macrocycle-assisted host-guest strategy is unique, owing to its self-complementary interactions and directional properties. The host-guest interactions have played a crucial…”
Section: Introductionmentioning
confidence: 99%
“…The concepts of supramolecular chemistry provide a natural translation of molecule constructions to create functional materials. [1][2][3] Supramolecular assemblies containing extended p-conjugated macrocycles are particularly attractive for applications in organic electronics/devices, 4,5 examples of note include cyclic porphyrins, 6,7 annulenes, 8-10 phenylenes [11][12][13][14][15] and oligothiophenes. [16][17][18] The most common building blocks of p-extended macrocycles are phenylenes, ethynylenes, thiophenes and pyrroles.…”
Section: Introductionmentioning
confidence: 99%